Unveiling the Antibacterial and Antioxidant Potential of Mentha longifolia: A Comprehensive Characterization of Ethanolic and Hexane Extracts - Itani, Dania; Hajj, Rana El (Edelweiss Applied Science and Technology, 2025)
Mentha longifolia, commonly known as wild mint, has been traditionally used for its medicinal properties. This study investigates the antimicrobial properties of hexane and ethanolic extracts from M. longifolia against selected bacterial and fungal strains. Various methods were employed to assess the antimicrobial activity, including agar disc diffusion and broth microdilution assays, while biofilm inhibition and destruction were tested using the crystal violet assay. The antioxidant activity was evaluated using the catalase enzyme assay. Additionally, phytochemical analysis was carried out to screen for possible bioactive components of M. longifolia extracts. Both ethanolic and hexane extracts demonstrated significant antibacterial and antifungal activities against all tested strains. Notably, both extracts exhibited a strong dose-dependent inhibition of biofilm formation and disruption of pre-formed biofilms. Moreover, the extracts effectively reduced catalase activity in bacterial cells, leading to oxidative stress-mediated toxicity. These effects are attributable to the presence of key bioactive compounds—phenols, flavonoids, terpenoids, quinones, tannins, and saponins—identified through phytochemical screening. Overall, the hexane and ethanolic extracts of M. longifolia demonstrate promising antimicrobial properties, suggesting their potential as natural alternatives for treating bacterial and fungal infections.